2021
DOI: 10.4018/ijwltt.286743
|View full text |Cite
|
Sign up to set email alerts
|

Personalized Learning Strategy as a Tool to Improve Academic Performance and Motivation of Students

Abstract: The purpose of the research is to study and scientifically substantiate personalized strategies as the basis for personalized learning aimed at improving academic performance and student motivation. The study involved 65 teachers and 700 students of various specialties from three Russian and Kazakhstan universities. The survey analysis showed that the modern generation of students is no longer motivated to receive standardized educational services, and in this context, personalized strategies as a form of pers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
1
4

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 47 publications
1
14
1
4
Order By: Relevance
“…Although numerous academic works claim that e-learning can enhance the overall desire to learn (Elfaki, Abdulraheem and Abdulrahim, 2019;Makhambetova, Zhiyenbayeva, and Ergesheva, 2021) and that the motivation for studying via the Internet is higher than when using a whiteboard and a projector in the class (Hoerunnisa, Suryani and Efendi, 2019), the outcomes of this study do not appear to corroborate this position.…”
Section: Discussioncontrasting
confidence: 90%
“…Although numerous academic works claim that e-learning can enhance the overall desire to learn (Elfaki, Abdulraheem and Abdulrahim, 2019;Makhambetova, Zhiyenbayeva, and Ergesheva, 2021) and that the motivation for studying via the Internet is higher than when using a whiteboard and a projector in the class (Hoerunnisa, Suryani and Efendi, 2019), the outcomes of this study do not appear to corroborate this position.…”
Section: Discussioncontrasting
confidence: 90%
“…A study by Makhambetova et al (2021) clearly demonstrated the components of individualized learning strategies. Individualized strategies help create a digital pathway for teachers to increase student achievement and motivation.…”
Section: Related Researchmentioning
confidence: 99%
“…Given students' difficulties during the distance learning period, lack of time to learn, self-learning skills can help extract and analyze data about the distance education process (Makhambetova et al, 2021).…”
Section: Conceptual or Theoretical Frameworkmentioning
confidence: 99%
See 2 more Smart Citations